Titik Nol Kehendak Berpemerintahan Sendiri (Zelfbestuur) 1916 Sarekat Islam: Sebuah Rekonstruksi Sejarah Masa Depan - Nunu A Hamijaya (PT. Student Rihlah Indonesia, 2026)
The purpose of this study is to analyze the history of the Zero Point of the Will for Self-Governance (Zelfbestuur) 1916 Sarekat Islam: A Reconstruction of Future History. This study employs a qualitative approach through literature review and reflective analysis. The methodological steps employed include Normative Analysis, Historical Analysis, and Reflective Analysis. The primary source, the book Zero Point of the Will for Self-Governance (Zelfbestuur) 1916, serves as the conceptual foundation and main reference. Based on the findings, ‘the will for self-governance (zelfbestuur)’ is a mantra. In the socio-political context of 100 (one hundred) years ago, this was a historic event for indigenous Muslims in the East Indies, after the power and sovereignty of many sultanates across the Nusantara region gradually weakened and eventually succumbed to Western colonial rule, with the last being the Sultanate of Aceh (1902). The struggle to achieve the ideal of self-governance for the indigenous Muslim people, pioneered by the Central Sarekat Islam, was in fact a metamorphosis and transformation of the substance of the sultanate or caliphate (Ottoman Turkey) governance model—one that was more egalitarian and non-feudal, relying on genealogy for succession. We must seek a new starting point agreed upon by the indigenous Muslim people of Indonesia today, so that the history of Zelbestuur from 100 years ago becomes not only a collective memory but also the driving force behind a shared movement to realize it in this millennium. From the perspective of historical scholarship, the NATICO I event certainly deserves attention through various national history seminars, enriched with documents and data. Indeed, from a political science perspective, the history of governance will also undergo reconstruction.